Blueberry muffin baby syndrome. A critical primary sign of systemic disease - Kaleta, Katarzyna; Kłosowicz, Agata; Juśko, Natalia; Kapińska-Mrowiecka, Monika (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Blueberry muffin baby syndrome is a rare and non-specific clinical presentation in newborns, characterized by the presence of widespread, maculopapular lesions of blue-red or violaceous colour and cohesive consistency [1]. The term “blueberry muffin baby” was initially coined to describe the skin manifestations of congenital rubella during the American epidemic in the 1960s [2, 3]. The presence of skin lesions is secondary to extramedullary hematopoiesis, which can result from intrauterine viral infections (TORCH syndrome), hematologic dyscrasias (twin-to-twin transfusion syndrome, hereditary spherocytosis, haemolytic disease of the newborn) or neoplasms (mastocytosis, histiocytosis, neuroblastoma, rhabdomyosarcoma, leukaemia) [1, 3].